Synthesis, biological evaluation and clinical trials of Cereblon-based PROTACs - André T. S. Vicente; Sara P. S. P. Moura; Jorge A. R. Salvador (Communications Chemistry)
Abstract PROteolysis-Targeting Chimeras (PROTACs) are an emerging class of molecules capable of inducing a forced approximation between a protein of interest (POI) and an E3 ligase enzyme (e.g., Cereblon), leading to the degradation of the POI by the cell’s own machinery. Although in early stages of development, PROTACs’ unique mechanisms of action offer a novel therapeutic strategy, which has attracted growing interest worldwide. Cereblon-based PROTACs are the most studied class of PROTACs and have been actively researched in recent years for the treatment of different diseases, from cancer to neurological disorders, with some of them already in clinical trials. In this review, we provide a comprehensive and critical analysis covering the recent advances, potential challenges and future prospects regarding the design and synthesis, as well as pre- and clinical evaluation of cereblon-based PROTACs. By integrating insights from drug discovery and development, a broad yet in-depth discussion is given to guide future research on cereblon-based PROTACs.